Genetic counseling in CHARGE syndrome: Diagnostic evaluation through follow up. Issue 4 (31st October 2017) - Hefner, Margaret A.; Fassi, Emily
Abstract : CHARGE syndrome (CS) is a complex genetic disorder causing multiple birth defects and sensory deficits (hearing, vision, balance, smell). Genetic counseling in CS must include not only the provision of factual information about CS, its cause, and inheritance, but also information about the developmental implications of CS features, referral to appropriate resources, and assistance with psychosocial adaptation to this information. CS should be considered in patients with any of the major diagnostic features: coloboma, choanal atresia, semicircular canal anomalies, or cranial nerve anomalies. The prime candidates in the differential are 22q11.2 deletion and Kabuki syndromes. Evaluation of features of CS, dysmorphology examination, and genetic testing can usually distinguish between the three conditions. Genetic counseling is important from early on, to help the family understand the process of genetic diagnosis, to interpret information coming from other specialists and to provide support and resources. Parents can easily be overwhelmed with the complexity of issues facing their child at diagnosis and in the future. CS is a substantial burden on a child, with high early mortality, multiple illnesses, hospitalizations and surgeries, and apparent medical fragility throughout life. The medical complexity of CS disrupts family life and contributes to delayed development. Multiple sensory deficits (impaired vision, hearing, and balance) further contribute to delayed motor and language development despite many individuals with CS having normal intelligence. Early referral to specialists in deafblindness and sensory deficits is essential. Resources are available to assist genetic counselors in diagnosis, follow‐up, and management of patients with CS.